Fetuin-A as a Potential Biomarker of Metabolic Variability Following 60 Days of Bed Rest - Ward, Kiera; Mulder, Edwin; Frings-Meuthen, Petra; O’Gorman, Donal J.; Cooper, Diane (Frontiers in Physiology, 2020)
Background: Fetuin-A is a hepatokine linked to the development of insulin resistance. The purpose of this study was to determine if 60 days head-down-tilt (HDT) bed rest increased circulating fetuin-A and if it was linked to whole body insulin sensitivity (IS). Additionally, we examined whether reactive jump training (RJT) could alleviate the metabolic changes associated with bed rest. Methods: 23 young men (29 ± 6 years, 181 ± 6 cm, 77 ± 7 kg) were randomized to a control (CTRL, n = 11) or RJT group (JUMP, n = 12) and exposed to 60 days of bed rest. Before and after bed rest, body composition and V.O2⁢p⁢e⁢a⁢k were measured and an oral glucose tolerance test was performed to estimate IS. Circulating lipids and fetuin-A were measured in fasting serum. Results: Body weight, lean mass, and V.O2⁢p⁢e⁢a⁢k decreased in both groups following bed rest, with greater reductions in CTRL (p < 0.05). There was a main effect of time, but not the RJT intervention, for the increase in fetuin-A, triglycerides (TG), area under the curve for glucose (AUCG) and insulin (AUCI), and the decrease in Matsuda and tissue-specific IS (p < 0.05). Fetuin-A increased in participants who became less insulin sensitive (p = 0.019). In this subgroup, liver IS and adipose IS decreased (p < 0.05), while muscle IS was unchanged. In a subgroup, where IS did not decrease, fetuin-A did not change. Liver IS increased (p = 0.012), while muscle and adipose tissue IS remained unchanged. Conclusions: In this study, we report an increase in circulating fetuin-A following 60 days of bed rest, concomitant with reduced IS, which could not be mitigated by RJT. The amount of fetuin-A released from the liver may be an important determinant of changes in whole body IS. In this regard, it may also be a useful biomarker of individual variation due to inactivity or lifestyle interventions.